Amplify-and-Forward Cooperative Diversity for Green UWB-Based WBSNs - Heba Shaban; Mohamad Abou El-Nasr (The Scientific World Journal)
This paper proposes a novel green cooperative diversity technique based on suboptimal template-based ultra-wideband (UWB) wireless body sensor networks (WBSNs) using amplify-and-forward (AF) relays. In addition, it analyzes the bit-error-rate (BER) performance of the proposed nodes. The analysis is based on the moment-generating function (MGF) of the total signal-to-noise ratio (SNR) at the destination. It also provides an approximate value for the total SNR. The analysis studies the performance of equally correlated binary pulse position modulation (EC-BPPM) assuming the sinusoidal and square suboptimal template pulses. Numerical results are provided for the performance evaluation of optimal and suboptimal template-based nodes with and without relay cooperation. Results show that one relay node provides ~23 dB performance enhancement at BER, which mitigates the effect of the nondesirable non-line-of-sight (NLOS) links in WBSNs.